A Meta-Analysis of the Dimensions of a Learning Organization Questionnaire: Looking Across Cultures, Ranks, and Industries. (May 2013) - Watkins, Karen E.; Dirani, Khalil M.
The Problem: Organizations strive to develop their employees to a level that meets current and future needs at a time when those needs are great and resources scarce. Human resource developers are charged with finding solutions; yet many of the changes essential to doing this are in the culture, and, senior leaders have greater impact on the culture. Effective ways to alert senior individuals to the cultural imperatives are needed. Unfortunately, human resource and organization development (HROD) scholars have had few valid organizational measures with which to demonstrate the status of learning and the impact of learning on the organization. In 2003, we shared the Dimensions of a Learning Organization Questionnaire (DLOQ) in this journal. It behooves us to examine what has occurred using this instrument since that time. The Solution: One approach is to build a self-sustaining learning architecture that is so embedded in the culture and even the work itself that it evolves and grows with the organization. A valid and reliable diagnostic enables HROD practitioners to assess where the learning culture is at the time of its administration, and signals organization members to critical changes needed to develop a more effective learning infrastructure. Armed with this information, they can make the business case and guide proposed interventions. Scholars can demonstrate key relationships between a learning culture and knowledge, financial, and mission performance. This article and others in this special issue examine what has been learned in the last decade using the DLOQ . The Stakeholders: HROD developers and senior leaders are significant stakeholders for this information. In addition, HROD scholars who hope to document the nature of the learning culture in a variety of contexts and to demonstrate the importance of having a strong learning culture to valued organizational outcomes will find a resource in the DLOQ .